Let's Get Theoretical: A Quantitative Content Analysis of Theories and Models Used in the Journal of Applied Communications - Lauri M. Baker; Audrey E. H. King (Journal of Applied Communications, 2016)
Theories and models are an important element in the progression of an academic field. This article focused on quantifying theories and models used in agricultural communication through a quantitative content analysis of the last 20 years of the Journal of Applied Communication (JAC). Specifically, the following research objectives guided this study: 1) describe characteristics (methods, number of authors) of articles in JAC, 2) identify which theories and models have been used in JAC, 3) determine how theory was used in JAC, 4) determine what characteristics predict the use of a theory or model in JAC. Researchers found 87 theories and models identified in JAC with 11 used five or more times and 19 that used between two and four times. Approximately 35% of the articles in JAC used a theory or model. Of those using a theory or model, the majority used it to inform the study, but rarely tested, created/built theory. Other results indicate the use of theory has increased in recent years and the number of authors and number of articles published. Implications for this study are a clear need for increased theoretical vigor in agricultural communication through increased focus on using theory to build on previous work in the industry.
Keywords: Journal of Applied Communications; Theory; Models; Agricultural Communication; Content Analysis